Mechanical Properties of Macaca fascicularis Amniotic Membrane and Duramater: A Potential Biomaterial for Dural Defect Closure - Ban Bolly, Hendrikus Masang; Rachmawati Noverina; Ahmad Faried (HM Publisher, 2024)
Background: The amniotic membrane (AM), a versatile biomaterial with inherent stem cells and extracellular matrix, has shown promise in various tissue engineering applications. Its potential as a dural substitute, particularly in addressing dural defects and preventing cerebrospinal fluid (CSF) leakage, has garnered increasing interest. However, a comprehensive understanding of the mechanical properties of non-human primate (NHP) AM, especially in relation to human AM, remains elusive. This knowledge gap hinders the optimal utilization of NHP models, such as Macaca fascicularis, in translational research for dural repair. This study aimed to characterize the mechanical properties of fresh Macaca fascicularis AM and dura mater and to investigate the influence of fetal gender, gestational age, and parity on AM mechanics. Methods: Sixteen fresh preparation amniotic membranes of Macaca fascicularis were obtained at the elective caesarean section that was already free of several infections, and three fresh preparation of dura mater of the same species were studied. The membranes were cut in specific sizes and then loaded at the Flavigraph (Textechno, Herbert Stein GmbH & Co.KG, Moenchengladbach, Germany) machine. The Young’s modulus, ultimate tensile strength, elongation at break, maximum elongation, and toughness of the amniotic membrane and dura mater were recorded and compared based on the fetal gender, gestational ages, and frequency of pregnancy. Results: This is the first report of mechanical properties of Macaca fascicularis amniotic membrane and dura mater. There are no statistically significant differences in mechanical properties of the amniotic membrane between the fetal gender, gestational age, and the frequency of pregnancy in fresh preparation amniotic membrane. The elasticity of the dura mater is seven times stiffer than the AM and the tensile strength of the dura mater is three times bigger than the AM, and the dura mater toughness is eight times bigger than the amniotic membrane. Conclusion: Our findings have shown the mechanical properties of Mf AM are not dependent on factors of fetal gender, gestational age, and frequency of pregnancy. This work provides an explanation of the physical properties of fresh preparation AM as the consideration to be used as allograft biomaterial in the dura mater substitution procedure.